2020
DOI: 10.1002/cphc.202000587
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Tyrosine and Structure‐Specific Intrinsic Fluorescence in the Fibrillation of Alzheimer's Associated Peptides

Abstract: Understanding of the structural changes during their aggregation and interaction is a prerequisite for establishing the precise clinical relevance of human islet amyloid polypeptide (hIAPP) (involved in Type-II Diabetes Mellitus) in the treatment of Alzheimer's disease stemmed from beta-amyloid (Aβ). Herein, we show that the steady-state emission spectra obtained from photoluminescence (PL) simultaneously capture both the tyrosine derivative (tyrosinate) and the structure-specific intrinsic fluorescence during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As aforementioned, Aβ and tau are two key biomarkers widely approved and extensively studied. The presence of electroactive groups, such as tyrosine, histidine, and methionine, in the Aβ structure enables the detection of this biomarker by recognizing oxidized peaks at ~0.6 V and 1.5 V, and waves at 1-1.5 V, respectively [109,112,113]. However, this approach is non-specific.…”
Section: Ad Biomarker Detection Methodologymentioning
confidence: 99%
“…As aforementioned, Aβ and tau are two key biomarkers widely approved and extensively studied. The presence of electroactive groups, such as tyrosine, histidine, and methionine, in the Aβ structure enables the detection of this biomarker by recognizing oxidized peaks at ~0.6 V and 1.5 V, and waves at 1-1.5 V, respectively [109,112,113]. However, this approach is non-specific.…”
Section: Ad Biomarker Detection Methodologymentioning
confidence: 99%
“…Many studies have demonstrated that Aβ can be completely detected by employing an electrochemical sensor to obtain a low LOD at picograms or femtograms per milliliter [ 53 , 63 , 64 , 67 , 69 , 70 , 71 , 82 ]. The Aβ peptide structure has a tyrosine group, histidine, and methionine which participate in the redox reaction with an oxidized peak at ~0.6 and ~1.05 and wave at 1–1.5 V vs. Ag/AgCl on a carbon surface [ 83 , 84 ]. The oxidation occurring on the residual groups under a supplied voltage indicates the detection ability for Aβ biomarkers; however, this method detects a plethora of other proteins containing such groups as well.…”
Section: Recent Research On Aβ Detection By Electrochemical Sensorsmentioning
confidence: 99%
“…Note that only relatively weak electric fields (a few V/mm) are required to affect the amorphous aggregates in comparison to those used to alter protein secondary structure and promote fibril formation 54,55 . The reason for this might be the weak inter-protein interaction within the amorphous aggregates.…”
mentioning
confidence: 99%